Multistage resection of esophageal squamous cell cancer of the cardia – successful despite complications - Zieliński, Jacek; Ptach, Anna; Sadowski, Andrzej; Chruścicka, Iwona; Pęksa, Rafał; Rak, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Surgery is the treatment of choice for squamous cell esophageal cancer. Complete resection of the esophagus with reconstruction of the digestive tract is performed for tumors located in the chest or cardia. The aim of the report is to present the case of a complete esophageal and gastric resection complicated by colon graft necrosis. The patient was a 45-year-old woman diagnosed with cancer of the cardia infiltrating the distal section of the esophagus and the body and fundus of the stomach. The initial surgical procedure included the opening of three body cavities followed by resection of the thoracic esophagus, stomach, and a portion of the left hepatic lobe. Right colon interposition was performed to restore digestive tract continuity. On the 8th day, a leak was observed in the esophagointestinal anastomosis. Management consisted in two surgical procedures, one of which ended in the removal of the colon patch. The fourth and final procedure was conducted after 10 months.